2019
DOI: 10.3390/ijms20225597
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease Monocytes Induce a Barrier Defect in Intestinal Epithelial Cells

Abstract: Intestinal epithelial barrier function in celiac disease (CeD) patients is altered. However, the mechanism underlying this effect is not fully understood. The aim of the current study was to evaluate the role of monocytes in eliciting the epithelial barrier defect in CeD. For this purpose, human monocytes were isolated from peripheral blood mononuclear cells (PBMCs) from active and inactive CeD patients and healthy controls. PBMCs were sorted for expression of CD14 and co-cultured with intestinal epithelial ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Tight junction indicators, ZO-1 and occludin, play indispensable roles in maintaining the intestinal mucosal barrier 49 . Our morphological results showed that the expression levels of the tight junction proteins (occludin and ZO-1) were reduced in SCZ mice, indicating increased intestinal permeability and impaired mucosal barrier, which were also observed in other diseases, such as in celiac disease 50 , IBD 51 , and diabetes 52 . However, drastically elevated expression of ZO-1 and occludin in the INU+SCZ group suggested that inulin could improve intestinal integrity and permeability, which was consistent with a previous study 39 .…”
Section: Discussionsupporting
confidence: 55%
“…Tight junction indicators, ZO-1 and occludin, play indispensable roles in maintaining the intestinal mucosal barrier 49 . Our morphological results showed that the expression levels of the tight junction proteins (occludin and ZO-1) were reduced in SCZ mice, indicating increased intestinal permeability and impaired mucosal barrier, which were also observed in other diseases, such as in celiac disease 50 , IBD 51 , and diabetes 52 . However, drastically elevated expression of ZO-1 and occludin in the INU+SCZ group suggested that inulin could improve intestinal integrity and permeability, which was consistent with a previous study 39 .…”
Section: Discussionsupporting
confidence: 55%
“…We evaluated the transcriptional changes of knocking down TRAFD1 in the monocyte-like cell line THP-1 under resting conditions (unstimulated) or in the presence of LPS, a known inducer of the NFκB pathway (Dorrington and Fraser, 2019 ). We selected this cell line considering the role of monocytes in modulating the epithelial barrier function and cytokine secretion in a CeD-specific context (Delbue et al, 2019 ), as well as for the technical ability to alter the expression of TRAFD1 using siRNA and the quick response of monocytes to LPS (Sharif et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD14 staining of the glycolipid-anchored membrane glycoprotein expressed on U937 cells enabled the identification of the pro-inflammatory-induced activation of the latter, which in the present study were greater following exposure to the higher gluten strength modern flour proteins. Interestingly, incubation of CD14 activated monocytes isolated from CD patients with cultured epithelial cells, resulting in an increase in TJ permeability, lower levels of occludin, and a mosaic expression pattern of ZO-1, an effect that was not evident following incubation with monocytes of healthy donors [ 48 ]. Given the potency of activated monocytes, the potential contribution of activated U937-monocyte-induced effects on Caco-2 cell TJ proteins cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%